2018
DOI: 10.1002/jbm.a.36421
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional coculture of primary hepatocytes and stellate cells in silk scaffold improves hepatic morphology and functionality in vitro

Abstract: A vigorous in vitro model of liver that could recapitulate hepatic phenotype and functionality in vivo would exclusively improve the efficiency of bioartificial liver, drug discovery, or even transplantation therapy. Owing to the indispensable role of three-dimensional (3D) microenvironment in supporting viability and function of hepatocytes in vitro, much effort recently has been focused on improving reproducibility and standardization of primary hepatocyte cultures with a paradigm shift to 3D culture system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, at this time point the cells in co-culture seemed to improve the metabolic function more than in the 3D system. However, the authors have not normalized these data, therefore, it cannot be ruled out that the positive effects seen in the 2D co-culture is only due to an improved survival of the hepatocytes [24]. Damania et al have published a cryogel coated with extracellular liver matrix which should mimic the natural ECM of the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at this time point the cells in co-culture seemed to improve the metabolic function more than in the 3D system. However, the authors have not normalized these data, therefore, it cannot be ruled out that the positive effects seen in the 2D co-culture is only due to an improved survival of the hepatocytes [24]. Damania et al have published a cryogel coated with extracellular liver matrix which should mimic the natural ECM of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these systems can barely be used for high-throughput methods. In addition, these systems have been explored so far mainly with rat hepatocytes instead of human ones [24,25,26], which makes the translation extremely difficult for testing of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Specically, primary rat hepatocytes seeded onto silk/chitosan scaffolds showed reduced inammatory response relative to synthetic scaffolds; 29 rat hepatocytes seeded onto silk/RGD scaffolds demonstrated improved gene expression for 3+ weeks over 2D culture; 30 co-cultures of rat hepatocytes and stellate cells in silk scaffolds demonstrated improved functions for 2 weeks than hepatocyte monocultures. 31 In human-relevant studies, the QZG human hepatic cells seeded onto silk/gelatin scaffolds demonstrated inltration of host cells aer implantation into a rodent model, 32 and cancerous HepG2 cells seeded onto silk/RGD scaffolds demonstrated improved gene expression over 2D culture. 30 While the studies above are promising for the use of silk/protein scaffolds for hepatocyte culture in vitro and implantation in vivo in animal models, the application of such scaffolds for long-term (1+ month) PHH cultures AE supportive non-parenchymal cells (NPC) has yet to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, silk degradation into non-toxic byproducts in vivo can be extended for months to allow native tissue remodeling. While silk scaffolds, in some cases with incorporated ECM proteins/gels, have been used to generate long-term tissue constructs for several different tissue types [20,22] as well as for the culture of rat hepatocytes +/-hepatic stellate cells for 2-3 weeks [23][24][25][26], it is not clear if silk scaffolds can support long-term PHH functions. Therefore, here we sought to determine for the first time the long-term function of PHHs in porous silk scaffolds +/-type I collagen.…”
Section: Introductionmentioning
confidence: 99%